Case 3784: Cnodalon Latreille, 1797 (Coleoptera, Tenebrionidae, Stenochiinae, Cnodalonini): proposed conservation of usage by designation of Cnodalon viride Latreille, 1804 as the type species - Bousquet, Yves; Bouchard, Patrice (Bulletin of Zoological Nomenclature, 2019)
The purpose of this application, under Articles 70.2 and 81.1 of the Code, is to preserve stability in the nomenclature of the beetle family Tenebrionidae by designating Cnodalon viride Latreille, 1804 as the type species of Cnodalon Latreille, 1797. The discovery that Cnodalon viride Latreille, 1804, currently considered the type species of the genus Cnodalon, is not an originally included nominal species in the genus Cnodalon, and so not available as the type species, results in disruptive nomenclatural changes in the family Tenebrionidae if another type species is selected.
Keywords: Nomenclature; taxonomy; Coleoptera; Tenebrionidae; Stenochiinae; Cnodalonini; type species